Porous single-crystalline molybdenum nitride enhances electroreduction of nitrogen to ammonia - Li, Xue; Xie, Kui (Frontiers in Materials, 2022)
The industrial ammonia synthesis reaction has the disadvantage of large energy consumption, thus the electrochemical reduction method of ammonia synthesis characterized by clean and environmental protection has received extensive attention. Molybdenum nitride is a commonly used electro catalyst for ammonia synthesis, and its Faraday efficiency is low, which may be due to many internal grain boundaries and few active sites. In this work, we grow microscale porous Mo2N single crystals and polycrystalline Mo2N from non-porous MoO3 single crystals. Porous molybdenum nitride materials facilitate charge transport in grain boundaries due to their single-crystal nature and enhance the catalytic properties of ammonia synthesis reactions. Compared with polycrystalline Mo2N, Porous Mo2N single crystal has better performance, with a high NH4+ yield of 272.56 μg·h-1 mg-1 and a Faradaic efficiency of 7.3%. In addition, porous Mo2N single crystal exhibits superior long-term stability with little attenuation after 16 h electrolysis reaction. It provides a new way for the catalyst of ammonia synthesis.